Sex difference in the association between metabolic syndrome and the risk of stroke: a systematic review and meta-analysis - Zhang, Lingling; Chi, Qi (Frontiers in Neurology, 2025)
BackgroundMetabolic syndrome comprises multiple cardiovascular risk factors, and previous studies have confirmed a significant association between metabolic syndrome and an increased risk of stroke. However, no systematic meta-analysis has evaluated the sex differences in the relationship between metabolic syndrome and stroke. This study aimed to investigate the sex difference in the association between metabolic syndrome and stroke.MethodsThe PubMed, Embase, and Cochrane Library databases were systematically searched for eligible studies until October 2024. The sex difference in the association between metabolic syndrome and the risk of stroke was calculated by relative risk ratio (RRR) with 95% confidence interval (CI) using a random-effects model with inverse variance weighting.ResultsNine studies involving 61,060 individuals were included in the meta-analysis. No sex difference was observed in the association between metabolic syndrome and the risk of stroke (RRR: 0.92; 95% CI: 0.72–1.17; p = 0.482). Sensitivity analysis found that the sex difference in this association was stable. Subgroup analyses revealed that male individuals with metabolic syndrome had a greater risk of stroke than female individuals in studies with a follow-up duration of <10.0 years (RRR: 0.70; 95% CI: 0.46–1.04; p = 0.078) and with low quality (RRR: 0.54; 95% CI: 0.30–0.98; p = 0.043).ConclusionSex differences may exist in the association between metabolic syndrome and the risk of stroke, especially with shorter follow-up periods. Further large prospective studies should be performed to verify the sex difference in the association between metabolic syndrome and the risk of stroke.